(untitled) (Bangladesh Journal of Livestock Research, 2021)
Foot and mouth disease (FMD) is a severe and highly contagious disease that causes immense financial losses due to mortality, reduced milk production, treatment cost of affected cattle, weight loss of fattening cattle and manpower loss for taking care of affected cattle, which occurs in Bangladesh almost every year. Outbreak of this disease causes financial loss to the farmers as well as the national economy of Bangladesh. Therefore, an attempt was made to assess the morbidity and mortality by FMD and to estimate financial loss incurred therein. For this study, data were collected from 850 affected households of Dhaka, Rajshahi, Rangpur, Khulna and Chattogram divisions of Bangladesh during July 2017 to June 2018 using a pre-tested interview schedule responding to the study objectives. In total, there were 4857 crossbred and 2138 native cattle in the affected household. The study revealed that the overall morbidity and mortality rates were 55.43% and 5.15%, respectively in crossbred cattle and 77.83% and 12.39%, respectively in native cattle and it differed significantly (p<0.01) with areas and category of cattle. Infection period for an FMD affected crossbred cattle were an average of 18.46±0.27 days and for native cattle were an average of 19.56±0.40 days. The total financial loss due to the FMD outbreak was calculated as Taka 53172067 (Tk. 53.17 million or US 0.63 million) for 850 affected households. The percentage of loss incurred was the highest for the death of affected cattle (63.47%) followed by veterinary cost (10.71%), weight loss of fattening cattle (10.68%), reduction in milk yield (9.17%) and manpower loss for taking care of affected cattle (5.98%). Based on this calculation the projected financial loss due to the FMD outbreak would be Taka 18856.96 crore (Tk. 188.57 billion or US 2.22 billion) per year in Bangladesh. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 82-94